2020
DOI: 10.1073/pnas.2003008117
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude and impact of the 431 CE Tierra Blanca Joven eruption of Ilopango, El Salvador

Abstract: The Tierra Blanca Joven (TBJ) eruption from Ilopango volcano deposited thick ash over much of El Salvador when it was inhabited by the Maya, and rendered all areas within at least 80 km of the volcano uninhabitable for years to decades after the eruption. Nonetheless, the more widespread environmental and climatic impacts of this large eruption are not well known because the eruption magnitude and date are not well constrained. In this multifaceted study we have resolved the date of the eruption to 431 ± 2 CE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…Marshall et al, 2019). While the majority of the potential chronological mismatches have been resolved using new ice-core chronologies and long-term hemispheric-wide treering-based climate reconstructions (Sigl et al, 2015;Stoffel et al, 2015;Wilson et al, 2016), several enigmas re-main. The most notable of these unsolved questions is the apparent discrepancy between the timing of two major sulfuremitting volcanic eruptions, including the largest sulfateloading event in the last 700 years, and large-scale climatic cooling observed during the 1450s CE (Esper et al, 2017).…”
Section: Assessing the Timing Strength And Climatic Impact Of Volcanmentioning
confidence: 99%
See 2 more Smart Citations
“…Marshall et al, 2019). While the majority of the potential chronological mismatches have been resolved using new ice-core chronologies and long-term hemispheric-wide treering-based climate reconstructions (Sigl et al, 2015;Stoffel et al, 2015;Wilson et al, 2016), several enigmas re-main. The most notable of these unsolved questions is the apparent discrepancy between the timing of two major sulfuremitting volcanic eruptions, including the largest sulfateloading event in the last 700 years, and large-scale climatic cooling observed during the 1450s CE (Esper et al, 2017).…”
Section: Assessing the Timing Strength And Climatic Impact Of Volcanmentioning
confidence: 99%
“…Briffa et al (1998) subsequently identified a distinct cooling event in 1453 CE, recorded at multiple sites within their circum-northern hemispheric network of tree-ring chronologies from the northern boreal forest, while Salzer and Hughes (2007) identified evidence for anomalous tree-ring growth in the early and late 1450s CE in western USA bristlecone pines. More recently, warm-season temperature reconstructions from Northern Hemisphere tree-ring networks have revealed spatially coherent and exceptional cooling in 1453 CE, with cooling ranging spatially between −0.4 and −6.9 • C, marking the onset of a 15-year cold period (Stoffel et al, 2015;Esper et al, 2017;Guillet et al, 2017).…”
Section: Timing Of Volcanic Eruptions In the 1450s Cementioning
confidence: 99%
See 1 more Smart Citation
“…Dates for eruptions that are not historically attested by a literate society are rarely known to a decade or century, let alone a calendar year. However, decadal or better accuracy dating of eruptions assumes great significance for events such as the Bronze Age eruption of Thera in the eastern Mediterranean (Friedrich et al, 2006;Pearson et al, 2018;Pearson et al, 2020;Friedrich et al, 2020) or the Tierra Blanca Joven eruption of Ilopango in Central America (Dull et al, 2019;Smith et al, 2020), which both occurred close to a literate society that may have been directly or indirectly affected.…”
Section: Introductionmentioning
confidence: 99%
“…The release of tens to thousands of cubic kilometers of magma producing widespread fallout and ground-hugging hot and turbulent pyroclastic flows are potential threats to life within large areas from the source (>100 km; Koch & Mclean, 1975;Wilson et al, 1995), while emissions of climate-forcing gases can have a global impact (Self & Blake, 2008;Sheets, 2015;Brenna et al, 2020Brenna et al, , 2021. One such devastating eruption was the variably dated 431-545 CE Tierra Blanca Joven (TBJ) eruption (∼106 km 3 ) from Ilopango caldera in El Salvador, Central America (Dull et al, 2019;Pedrazzi et al, 2019;Smith et al, 2020). During this eruption, densely populated Maya settlements were buried under pyroclastic deposits (∼40,000-80,000 casualties; Dull et al, 2019;Hart & Steen-McIntyre, 1983) causing a profound reorganization of the Maya society at political, economic, and demographic levels (Dull et al, 2001(Dull et al, , 2019Sheets, 2015).…”
Section: Introductionmentioning
confidence: 99%